Arthroscopic treatment of synovial chondromatosis of the ankle - Daniel Peixoto; Marta Gomes; António Torres; António Miranda (Revista Brasileira de Ortopedia)
ABSTRACT Synovial chondromatosis is a rare proliferative disease, characterized by the occurrence of metaplasia in the synovium of the joints. These lesions become pedunculated; with the evolution of the disease they become detached, leading to intra-articular loose-bodies. It occurs more frequently in males between the third and fifth decades of life, usually affecting large joints such as the knee and hip. Smaller joints, such as the ankle, are less frequently affected. Patients report articular pain, blockage, and limited range of motion caused by the loose fragments. As the disease progresses, the joint undergoes degenerative changes. This report describes a case of synovial chondromatosis of the ankle, treated by arthroscopy. The patient, a 59 year-old male, complained of pain and swelling of the left ankle. Physical evaluation showed limited tibiotarsal mobility (plantar flexion of 20° and dorsiflexion of 5°). After physical and imaging evaluation, the patient underwent ankle arthroscopy due to impingement of the joint, with limitation of mobility. Arthroscopic treatment allowed easy access to the joint, removal of loose bodies, and partial synovectomy, with low morbidity and early rehabilitation. The final prognosis was excellent.